Determinants of Firm Performance: An Empirical Evidence from Construction Industry in Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The construction industry is the 4th largest contributing industry togross domestic product in 2016 in Indonesia. However, its’ growth is slowingdown recently because of the companies’ low competitiveness that causesproduction inefficiency. Despite the urgency for a comprehensive solution toincrease its productivity, research in this area is still lacking. This study aimsto examine the development and application of electronic customerrelationship management (e-CRM) theory, project innovation (PI), projectorganizational culture (BO), and dynamic capabilities (KD) in increasingcompetitive advantage (KB), and its implications for business performance(KP), moderated by the size of construction companies in Indonesia.Bycollaborating with PT BCI Asia for data collection, at least 200 responses aretargeted to collect from online questionnaires and analyzed by structuralequation modeling (SEM). We found that (1) there is a significant influence ofe-CRM, PI, and KD on KB; (2) there is an influence of PI, BO, and KD onKP, while e-CRM has no significant effect; (3) there is a significant influenceof KB on KP in Indonesian construction firm; (4) KB mediates the influenceof e-CRM, PI, BO, and KD on KP; and (5) firm size moderates the effect ofKB on KP.